Hungarian Monitoring, 27 November 1989 . [Magyar rádiófigyelő], 1989. november 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Czechoslovak events: extraordinary Central Committee session, general strike - Common Market foreign ministers' meeting - American troop withdrawals from Europe - Baltic republics' economic independence Domestic Affairs: - Partial referendum results - Evaluating the four-party coalition - Warsaw Pact meeting in Budapest - Miners' trade union congress - "Magyar Nemzet" (Hungarian Nation) daily paper becomes public limited company Economy: - Judgment of the tax law - Pét Nitrogen Works sold - Agriculture and the Common Market Külpolitika: - Csehszlovák események: rendkívüli KB ülés, általános sztrájk, - A Közös Piac külügyminiszteri ülése - Amerikai csapatkivonások Európából - A balti köztársaságok gazdasági önállósága Belpolitika: - Részadatok a referendum eredményeiről - A négypárti koalíció értékelése - VSZ találkozó Budapesten - Bányász szakszervezeti kongresszus - Rt.-vé alakul a Magyar Nemzet Gazdaság: - Adótörvény bírálata - Elkelt a Péti Nitrogénművek - Mezőgazdaság és Közös Piac